2018
DOI: 10.18502/kls.v4i1.1373
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk Factors of Dengue Hemorrhagic Fever (DHF) In Rural Populations in Panongan Subdistrict, Tangerang 2016

Abstract: DHF is a disease that affects the population in urban areas. But several recent research groups. The analysis used was a logistic regression analysis. The analysis showed a significant association between sex (4,99; 2.05-12.14) and mobility (2.28; 1.20-4.35) with the incidence of dengue. This research concludes that sex is the most dominant variable related to the incidence of DHF with OR = 4,17. It means that males have 4,17 times higher risk of acquiring DHF compared to females after controlling the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…[19][20][21] Based on Malaysia's surveillance data, adult males had a 4.17 times greater risk of contracting dengue in contrast to females. 24,25 Our analysis revealed that the male and female ratio in dengue cases was 1.57:1, while in SD the ratio was increased to 4:1. The difference in gender was significant (p = 0.0005) and these were in agreement with other former studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…[19][20][21] Based on Malaysia's surveillance data, adult males had a 4.17 times greater risk of contracting dengue in contrast to females. 24,25 Our analysis revealed that the male and female ratio in dengue cases was 1.57:1, while in SD the ratio was increased to 4:1. The difference in gender was significant (p = 0.0005) and these were in agreement with other former studies.…”
Section: Discussionmentioning
confidence: 69%
“…22 Our findings indicate that older subjects were at high risk for SD as increased age is associated with the presence of comorbidities and altered level of immunity. 23,24 Males were reported to contract dengue more, in contrast to females. The percentage of males infected with dengue was higher in several studies ranging from 60.0% to 63.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between these factors and the use of K3EDTA anticoagulants could be the cause of no significant differences between NS1 (+) and NS1 (-). 11,14 The results of a differential count examination, especially the number of lymphocytes and basophils did not increase. Monocyte cell counts had a slight increase where on the NS1 (+) group monocyte count was 8.26% and NS1 (-) group was 8.76%.…”
Section: Resultsmentioning
confidence: 89%
“…Age is related to daily activities inside and outside because Aedes Sp has a biting habit in the morning and evening. 11 The results of different tests for the sex group and age between NS1 (+) and NS1 (-) showed that there were no significant differences. This happens because NS1 affects the severity of dengue disease but does not depend on the sex and age of the host.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation